Republic of Kazakhstan : Report on the Observance of Standards and Codes (ROSC)-Data Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Report on the Observance of Standards and Codes (ROSC) data module provides a review of Kazakhstan's data dissemination practices against the IMF's General Data Dissemination System. The quality of Kazakhstan's macroeconomic statistics has improved significantly in the last few years. The authorities have established a good track record of implementing recommendations of past technical assistance missions in the area of statistics, and have demonstrated commitment to pursue plans and programs to further improve their statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet